2005
DOI: 10.1029/2005wr004084
|View full text |Cite
|
Sign up to set email alerts
|

Water, salt, and energy balances of the Dead Sea

Abstract: [1] The Dead Sea is a hypersaline terminal lake experiencing a water level drop of about 1 m/yr over the last decade. The existing estimations for the water balance of the lake are widely variable, reflecting the unknown subsurface water inflow, the rate of evaporation, and the rate of salt accumulation at the lake bottom. To estimate these we calculate the energy and mass balances for the Dead Sea utilizing measured meteorological and hydrographical data from 1996 to 2001, taking into account the impact of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
152
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(164 citation statements)
references
References 32 publications
3
152
0
1
Order By: Relevance
“…Therefore, in case important water exchanges between the VCL and the aquifer occur, they would decrease the surface water salinity and contribute to lowering the longitudinal salinity gradients along the system, because the groundwater salinity is not being evapoconcentrated as in the VCL2. Regarding the volume conservation in the entire system, the inverse relationship between the net evaporation rate and water salinity (Oround 1999;Lensky et al 2005) should be included in the computation of the actual evaporation rates from VCL2. According to Oround (1999) and Lensky et al (2005), this inverse relationship decreases the water saturation in the air because of reductions in the free energy of water molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in case important water exchanges between the VCL and the aquifer occur, they would decrease the surface water salinity and contribute to lowering the longitudinal salinity gradients along the system, because the groundwater salinity is not being evapoconcentrated as in the VCL2. Regarding the volume conservation in the entire system, the inverse relationship between the net evaporation rate and water salinity (Oround 1999;Lensky et al 2005) should be included in the computation of the actual evaporation rates from VCL2. According to Oround (1999) and Lensky et al (2005), this inverse relationship decreases the water saturation in the air because of reductions in the free energy of water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the volume conservation in the entire system, the inverse relationship between the net evaporation rate and water salinity (Oround 1999;Lensky et al 2005) should be included in the computation of the actual evaporation rates from VCL2. According to Oround (1999) and Lensky et al (2005), this inverse relationship decreases the water saturation in the air because of reductions in the free energy of water molecules. To take into account this process, the parameter b is introduced such that the evaporated mass E kg m 22 s 21 is computed as…”
Section: Resultsmentioning
confidence: 99%
“…Alpert et al [17] showed that evaporation rates in the evaporation ponds of the Dead Sea southern basin have increased during the last decades due to the shrinkage of the northern basin. Recently, Lensky et al [5] had developed a model to estimate the water balance of the lake that reflects the unknown subsurface water inflow, the rate of evaporation, and the lake of salt accumulation at the lake bottom. The evaporation process on free water surface of the Dead Sea is modeled based on the following two approaches: 1) Mass balance approach and 2) Energy balance approach.…”
Section: Mass and Energy Balancesmentioning
confidence: 99%
“…Over 43 billion tons of salts are thought to be available in the Dead Sea, of which almost 2 billion tons are Potassium Chloride [4] . The volume of the Dead Sea is about 132 km 3 , with surface area of about 625 km 2 , maximum depth of about 300 m and surface level at about 418 m below minimum sea level [5] . More general information about the Dead Sea water composition and reserves are shown in Table 1 [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation